Disentangling the American Christian Right: An Interview with Dr. Christopher Douglas | Decifrando a direita cristã norte-americana: uma entrevista com o Prof. Dr. Christopher Douglas - Lopes, Lucas da Silva (Reflexão, 2019)
Christopher Douglas is one of the most prominent scholars who has studied the rise of the conservative Christian Right in the American political arena and the links of this complex movement to American culture. Prof. Douglas taught at the University of Toronto and, for five years, at Furman University, South Carolina before transferring to University of Victoria in 2004. He teaches American literature, particularly contemporary American fiction, religion and literature, multicultural American literature, postmodernism, and the Bible as Literature. In the interview below, Prof. Douglas talks about his research and the idea behind his book “If God Meant to Interfere”, published in 2016; the explanatory concepts of Christian Multiculturalism and Christian Postmodernism; the spread of fake news, conspiracy theories, and alternative facts among Christian fundamentalists; the American political context. Prof. Douglas also offers interesting comments on the current Brazilian situation. His critical insights provide interesting and new perspectives that give fresh vitality to the debates about Christian fundamentalism. Prof. Douglas is committed to “public-scholar engagement” that is, research-based critical writings for non-academic audiences. Links to his public academic activity are inserted throughout the interview.